Intralingual Translation Procedures in Nihon NO Uta - Amri, Miftachul; Rusmiyati, Rusmiyati; Adhimas, Yogi Bagus; Birri, Iffa Mar’atus Shohibul; Zulmi, F A. Z.; Irawati, Fitriana Dewi (Journal of Social Science and Business Studies, 2024)
The purpose of this study is to analyze how intralingual translation procedures are used in translating modern Japanese songs into classical Japanese. This study used a descriptive qualitative method with Vinay and Darbelnet's translation procedures theory to explain the process of intralingual translation. The results of the study showed that the song translated influenced the use of translation procedures. For example, the song "千本桜" by Kuro Usa-P uses adaptation translation procedures, that is 18 of 30 data, "夜に駆ける" by YOASOBI uses literal translation procedures, that is 24 of 34 data, and then "ドライフラワー" by Yuuri uses equivalence translation procedures, that is 13 of 23 data. The use of literal translation procedures has the highest frequency, which is 32 data out of 87 data. However, it is important to note that the procedures used are very dependent on the translator, as the translator is free to determine the translation procedures they want to use.